Aspects of planning in relation to Claremont shopping centre - Tomalin, Peter N (School of Architecture, Planning and Geomatics, 2016)
The activity with which this thesis is concerned is that of retailing; the area of focus being the shopping centre. This environment is one which displays a complex set of spatial and human relationships involving amongst others location, size, rent structure, shopping mix, movement, fashion, socio-economic status, expenditure patterns and consumer behaviour. It can be demonstrated that if certain of these factors are left to respond to what is generally known as the "market mechanism", the resultant environment usually exhibits certain undesirable features such as congestion, pollution and commercial blight. The planner seeks, amongst other aims to create an environment which is optimal and balanced and which provides for human needs such as convenience and safety.